Nanostructure reorganization in a thermotropic copolyester. A simultaneous WAXS and SAXS study1. (5th November 2015) - Reyes‐Mayer, A.; Alvarado‐Tenorio, B.; Romo‐Uribe, A.; Benavente, R.; Jaffe, M.; Molina‐Ocampo, A.
Abstract : Thermally induced Angstrom and nanometer‐scale reorganization in thermotropic liquid crystalline polymer based on (1, 4)‐hydroxybenzoic acid (B) and (2, 6)‐hydroxynaphthoic acid (N) was investigated by simultaneous wide‐angle and small‐angle X‐ray scattering (SAXS, respectively). Extruded tapes 50 µm thick were annealed at 240°C under dry air conditions. The as‐received tape exhibited fiber‐like structure with crystalline order, whereas the SAXS patterns exhibited diamond‐shaped diffuse scattering elongated along the equatorial axis elucidating nanovoid morphology oriented along the extrusion axis. Guinier analyses showed that the radius of gyration Rg of nanovoids were ca. 17 nm along the extrusion axis. Heat treatment produced a sharpening of the 002 meridional reflection and the 110 equatorial reflection suggesting an improvement of molecular register and packing. The molecular alignment, as quantified by the order parameter P ¯ 2, increased as well as the degree of crystallinity χ . On the other hand, SAXS intensity along the equatorial axis decreased evidencing reduction of Rg, i.e. lateral compression of the nanovoids and better molecular packing. Thermal treatment increased the thermal stability and the uniaxial tensile Young's modulus, E, along extrusion axis. However, the tapes exhibited microhardness anisotropy and the indentation anisotropy, ∆H, gradually decreased suggesting reduction of elastic recovery in the molecular chain direction. Scanning electron microscopy evidenced an outer skin with an internal layered morphology that transformed into sheet‐like morphology with meandering fibrils. This investigation evidenced microstructure and morphology reorganization correlating with improved thermal and mechanical properties. Copyright © 2015 John Wiley & Sons, Ltd.